Early Recurrence and Cerebral Bleeding in Patients With Acute Ischemic Stroke and Atrial Fibrillation. Issue 8 (August 2015) - Paciaroni, Maurizio; Agnelli, Giancarlo; Falocci, Nicola; Caso, Valeria; Becattini, Cecilia; Marcheselli, Simona; Rueckert, Christina; Pezzini, Alessandro; Poli, Loris; Padovani, Alessandro; Csiba, Laszló; Szabó, Lilla; et al.
<x xml:space="preserve">Abstract</x> Background and Purpose— The best time for administering anticoagulation therapy in acute cardioembolic stroke remains unclear. This prospective cohort study of patients with acute stroke and atrial fibrillation, evaluated (1) the risk of recurrent ischemic event and severe bleeding; (2) the risk factors for recurrence and bleeding; and (3) the risks of recurrence and bleeding associated with anticoagulant therapy and its starting time after the acute stroke. Methods— The primary outcome of this multicenter study was the composite of stroke, transient ischemic attack, symptomatic systemic embolism, symptomatic cerebral bleeding and major extracranial bleeding within 90 days from acute stroke. Results— Of the 1029 patients enrolled, 123 had 128 events (12.6%): 77 (7.6%) ischemic stroke or transient ischemic attack or systemic embolism, 37 (3.6%) symptomatic cerebral bleeding, and 14 (1.4%) major extracranial bleeding. At 90 days, 50% of the patients were either deceased or disabled (modified Rankin score ≥3), and 10.9% were deceased. High CHA2DS2-VASc score, high National Institutes of Health Stroke Scale, large ischemic lesion and type of anticoagulant were predictive factors for primary study outcome. At adjusted Cox regression analysis, initiating anticoagulants 4 to 14 days from stroke onset was associated with a significant reduction in primary study outcome, compared with initiating treatment before 4 or after 14 days: hazard ratio 0.53 (95% confidence interval 0.30–0.93). About 7% of the patients treated with oral anticoagulants alone had an outcome event compared with 16.8% and 12.3% of the patients treated with low molecular weight heparins alone or followed by oral anticoagulants, respectively (P=0.003). Conclusions— Acute stroke in atrial fibrillation patients is associated with high rates of ischemic recurrence and major bleeding at 90 days. This study has observed that high CHA2DS2-VASc score, high National Institutes of Health Stroke Scale, large ischemic lesions, and type of anticoagulant administered each independently led to a greater risk of recurrence and bleedings. Also, data showed that the best time for initiating anticoagulation treatment for secondary stroke prevention is 4 to 14 days from stroke onset. Moreover, patients treated with oral anticoagulants alone had better outcomes compared with patients treated with low molecular weight heparins alone or before oral anticoagulants.